Deviations from the balanced time perspective, cognitive fusion, and self-compassion in individuals with or without a depression diagnosis: different mean profiles but common links to depressive symptoms - Pyszkowska, Anna; Åström, Elisabeth; Rönnlund, Michael (Frontiers in Psychology, 2024)
Introduction Prior research indicates that depressive symptoms in unselected or sub-clinical samples are associated with time perspective biases, including a more negative view of the past and a more fatalistic attitude toward the present. In the current study, we compared time perspective profiles for a clinical sample, with a depression diagnosis with that of a control group. Additionally, we considered a measure known as deviations from the balanced time perspective (DBTP) that capture deviations across time frames, not considered in previous studies. A second obejctive was to test a model involving DPTP as a mediator of the links between cognitive fusion and self-compassion with depressive symptoms. Method In total, 300 individuals participated in the study, 150 participants with a depression diagnosis and 150 without a depression diagnoses. All participants filled in questions regarding background variables together with Polish adaptations of ZTPI, CFQ, SCS-S, and DASS-21 using a web-survey. Results The results showed significantly higher scores on Past Negative and Present Fatalistic in the clinical sample. In line with the hypothesis the clinical group also displayed elevated DBTP scores (d = 0.75), a difference that remained significant when current symptoms were adjusted for. The results of structural equation modeling moreover indicate a major role of cognitive fusion (which, as expected, was strongly associated with DBTP) in predicting symptom burden, regardless of the clinical/non-clinical distinction, but. Still, DBTP accounted for significant (unique) variance in depressive symptoms. By contrast, the inclusion of cognitive fusion and DBTP eliminated the association of self-compassion and depressive symptoms. Conclusion Taken together, the results indicate that levels of DBTP/fusion for persons with depression diagnosis is present regardless of current symptom burden. Thus, DBTP could be regarded as a risk factor of developing depression. Prospective research designs are needed to further evaluate the associations of the main constructs in this study and the extent to which they are predictive of future diagnosis and changes in symptom level.